Transformations of the historical context in the linguistic consciousness: Ideas, idols, and ideals - M.A. Pilgun (Ученые записки Казанского университета: Серия Гуманитарные науки)
The present paper is of high relevance, because this year marks the 100th anniversary of the events of 1917, which forces us to reconsider the situation of that time. The subjects of the study are reflections of the ideological paradigm of the October Revolution in the consciousness of today's young Russian people. The purpose of the study is to analyze changes in the attitude to the events of 1917 and the opinion of the modern Russian Society on them. The empirical material was investigated using content analysis with the AutoMap software. The results of the study show that young people today think that the October Revolution of 1917 is an important event of the 20th century, only, while the February Revolution is almost missing in their linguistic consciousness. The most popular is the idea of social justice. Among the historical characters of the events of 1917, the images of Lenin and Stalin stand out. The study has also revealed the high efficiency of the sacred ideals of Christianity as the basis for the formation of a new world order idols in Russia.